(untitled) (Proceedings of the European Wave and Tidal Energy Conference, 2025)
Reliable turbulence measurements are essential for deploying underwater tidal energy due to the effect of unsteady flow on turbine performance and lifespan. This paper investigates the application of motion-correction techniques to a novel turbulence sensor, the Barnacle, for more accurate turbulent flow estimation. Instrument deployment was conducted in Strangford Narrows during October and November 2024 from a floating flow-facing offshore barge, with multiple Barnacles validated against a Nortek Vector ADV. Preliminary validation of the smaller Barnacle probe indicated good streamwise-normalised median velocity agreement of within 20% in all three directions for a long-term 12-hour deployment. Motion-corrected median TKE and median streamwise TI were also within 12% of the Vector-derived values and agreed with previously published data from the deployment location. While Vector data were used to correct for acceleration-induced contamination due to limitations of the inertial measurement unit of the Barnacles, this will be rectified in future work to further improve motion correction.